Speech Act Analysis of Harry and Meghan’s Interview with Oprah Winfrey on CBS Morning News Show - Rifai, Irfan (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
This article is aimed at finding out types of illocutionary acts found in one of the most shocking viral interviews in the world, that is the interview with the royal family of former member, Harry and Meghan Markle interviewed by Oprah Winfrey, with amount of viewership of 4.79 million viewers when it first shows on air. This research is framed within mixed-method approach where the results of the study are in the form of an overview of what is said (illocutionary acts) by the three main subjects, namely Harry, Meghan, and Oprah and the percentage of each type of illocutionary acts. Data analysis was conducted through the analysis of interview videos along with the transcripts, simple statistical analysis and is supported by literature study. The results of the current study show that from 319 data of 644 sentences indicated as illocutionary acts. From those findings, it can be categorized that there are five types of illocutionary acts were found in an interview, they are 63% assertive, 27% directives, 0,6% commissive, 7,3% expressive, and 0,3% declarative. In other words, assertive is found to be the dominant type of illocutionary acts. In addition, of the 319 data, 295 data are categorized as direct speech act and 24 data are indicated as indirect speech act. In short, illocutionary acts of assertive type and direct speech acts are found to be more dominant in Harry and Meghan interview with Oprah Winfrey.